Anomalies and variant anatomy of the aorta and the supra-aortic vessels: additional challenges met by hybrid procedures - Setacci, F (EDIMES Edizioni Internazionali Srl, 2009)
INTRODUCTION: Endovascular or hybrid approach to the aortic arch aneurysms is nowadays an appealing solution for selected patients. Aim of this retrospective study is to evaluate the technical and clinical success recorded in complex anatomical settings of endografting. METHODS: Between December 2004 and December 2008, 73 patients were treated with a stent-graft for thoracic aorta aneurysms at our Vascular and Endovascular Surgery center, or in other Italian Centers by our Vascular Surgeon as Proctor. The aortic arch was involved in 31 cases. Four cases of bovine arch, three aberrant right subclavian artery and one case of isolated origin of all the supra-aortic trunks (6 vessels) were recorded. Technical success, procedural planning time and procedural time, stroke and paraplegia incidences were analyzed in terms of difference between “normal” or “complex” arches. RESULTS: Technical success was achieved in all cases. Complex anatomy of the arch and the supra-aortic trunks increased the technical difficulty of endovascular exclusion of the aneurysm and required more often complex debranching of the supra-aortic vessel necessary to obtain an adequate landing zone and to preserve the brain and spinal cord perfusion. We observed one stroke in complex arches procedures and two strokes (one of them fatal) in normal arch procedures. No cases of paraplegia were observed. CONCLUSIONS: In our experience complex anatomy of the arch did not represent a predictive factor in term of peri-procedural major neurological adverse events.